Systemic inflammatory response syndrome after pediatric congenital heart surgery: Incidence, risk factors, and clinical outcome. Issue 2 (7th December 2016) - Boehne, Martin; Sasse, Michael; Karch, André; Dziuba, Friederike; Horke, Alexander; Kaussen, Torsten; Mikolajczyk, Rafael; Beerbaum, Philipp; Jack, Thomas
Abstract: BACKGROUND: Systemic inflammatory response syndrome (SIRS) is frequent after cardiac surgery, but data on its incidence and perioperative risk factors are scarce for children with congenital heart disease. METHODS: SIRS incidence within 72 hours following cardiac surgery was evaluated in a secondary analysis of children enrolled to a treatment‐free control group of a randomized controlled trial. Intraoperative parameters were investigated for their association with SIRS using multivariable fractional polynomial logistic regression models. Effects of SIRS on various organ functions and length of stay were evaluated using time‐varying Cox regression models. RESULTS: In 116 children after cardiac surgery (median age [range]: 7.4 month [1 day‐16.2 years]) SIRS occurred in n = 39/102 with and n = 1/14 without cardiopulmonary bypass (CPB). Duration of CPB (hazard ratio [HR]: 2.28 per hour; 95% confidence interval [CI] 1.17; 4.42) and amount of fresh frozen plasma (HR: 1.23 per 10 mL/kg; 95%CI 1.06; 1.42) were identified as predictors for SIRS; neonates seemed to be less susceptible for SIRS development (HR: 0.86; 95%CI 0.79; 0.95). SIRS was associated with organ dysfunction (HR: 2.69; 95%CI 1.41; 5.12) and extended stay in the pediatric intensive care unit (PICU) (median: 168 vs. 96 hours; p = 0.007). CONCLUSIONS: SIRS is a frequent complication after pediatric congenital heart surgery; it affects nearly one third of children and prolongs PICU stay significantly. Duration of CPB and amount of fresh frozen plasma were identified as important risk factors. Neonates seem to be less susceptible to SIRS development.